Enzyme-instructed self-assembled supramolecular bi-antibodies for inhibition and imaging of atherosclerosis progression - Shuang Bian; Yangang Zhu; Nanxin Zhao; Yanchen Wang; Zhimou Yang; Jingjing Li (Materials Today Bio)
Atherosclerosis (AS) is characterized by lipid overaccumulation and progressive chronic inflammation. Macrophages over-accumulate at plaque sites and promote fibrous cap instability and plaque rupture by participating in lipoprotein uptake and metabolism, inflammatory factor secretion, and the production of enzymes and toxic metabolites. The macrophages accumulating at plaque sites are mainly derived from circulating blood-derived monocytes. Therefore, we designed a peptide 2P with an alkaline phosphatase (ALP) induced self-assembly function and P-selectin targeting function to form a supramolecular bi-antibodies 2P@VLA-4 by coassembling with VLA-4, a CD106 affinity. The dephosphorylation site and efficiency were optimized. 2P@VLA-4 displayed enhanced protein stability and binding ability to inflamed vascular endothelial cells. Through the dual-targeted blocking effect on the adhesion binding site of monocytes, 2P@VLA-4 could significantly reduce the accumulation of monocytes/macrophages at the plaque site, thereby inhibiting the progression of AS. At the same time, modification of peptides with fluorescent molecules enabled specific imaging of plaques. This study focused on the ease of design and functionalization of peptides, to synthesize supramolecular bi-antibodies compound innovatively by enzyme instructed self-assembly (EISA), achieving the significant inhibition of the adhesion and aggregation of monocytes at plaque sites. Coupling with its specific imaging capability, it may provide new approaches for the integrated design of diagnosis and treatment of AS.